Homestay Service Digitalization, Tourist Satisfaction, and Loyalty: The Mediating Role of Trust - Mahdha Nafilata Aulia Az-zulfa; Fatkhur Rohman Albanjari; Sri Hartono (Lembaga Bale Literasi, 2026)
The rapid development of digital technology has significantly transformed the tourism industry, including homestay services that increasingly rely on digital platforms to improve customer experiences. However, the adoption of digital services among community-based homestays remains uneven, particularly in rural tourism destinations, creating challenges in maintaining tourist satisfaction, trust, and loyalty. This study aims to examine the effects of homestay service digitalization and tourist satisfaction on tourist loyalty through the mediating role of trust at Telaga Sarangan Tourism Destination, Magetan, Indonesia. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from tourists who had stayed in homestays around Telaga Sarangan through structured questionnaires measured using a five-point Likert scale. The measurement model was evaluated through convergent validity, discriminant validity, composite reliability, and Cronbach's alpha, while the structural model was assessed using path coefficient analysis and bootstrapping. The findings indicate that homestay service digitalization significantly enhances tourist trust and loyalty. Tourist satisfaction also exerts significant positive effects on trust and loyalty. Furthermore, trust plays a significant mediating role in strengthening the relationships between homestay service digitalization and tourist loyalty as well as between tourist satisfaction and tourist loyalty. These findings suggest that improving digital service quality and enhancing tourists' satisfaction are essential strategies for increasing trust and fostering long-term tourist loyalty. The study contributes to the literature on digital tourism by highlighting the strategic role of trust in strengthening loyalty within community-based homestay services in rural tourism destinations.